Identifying social norms in physical aspects of food environments: A photo study. (1st December 2019) - Raghoebar, Sanne; van Rongen, Sofie; Lie, Rico; de Vet, Emely
Abstract: It is widely accepted that physical food environments can contribute to unhealthy eating, but less is known about how physical cues in these environments actually stimulate eating. Our study starts from the assumption that social norms are embedded in physical cues and aims to make an inventory of physical cues that communicate what is socially accepted as normal and/or appropriate to eat in a Dutch outside-the-home food context. In Study 1, we conducted a qualitative study in which photographs taken in self-service food environments were analyzed using strategies from photo documentation and semiology. Grounded theory was applied to identify a wide variety of specific physical cues that were ultimately grouped into 18 higher level categories of physical cues (e.g. consumption traces, product availability). Most cue categories were associated with either descriptive or injunctive social norms, but some were associated with both types. In Study 2, we aimed to quantitatively cross-validate the social norm interpretations among laypeople ( N = 173) by focusing on two selected photographs. More than half of the physical cues that participants identified in these photographs as being influential had been identified in Study 1 as cues bearing a normative message. The results further indicated that other people's behavior is easier to recognize in physical food environments than signals about what ought to be done. Given the great variety of identified physical cues associated with social norms, we posit that social norms are widely embedded in food environments and might guide eating behavior. Further research should study the effects of these cues on behavior and test whether the underlying process can be attributed to social norm interpretations.